The Effect of the Installation Angle of the Sky Quality Meter on the Night Sky Brightness and the Beginning of the Fajr Prayer Time - Raisal, Abu Yazid; Hidayat, Muhammad; Hermawan, Leo; Rakhmadi, Arwin Juli (Indonesian Review of Physics (IRiP), 2020)
Measuring the brightness of the night sky and determining the start of Fajr prayer times can be done using SQM. Observations were made at OIF UMSU with coordinates 3o 34' 55.06" N and 98o 43' 17.09" E. The sky brightness was measured using three SQMs mounted facing the zenith, eastern horizon, and western horizon. The night sky brightness values for SQM directed to the zenith, eastern horizon, and western horizon are 18.23 mpsas, 15.82 mpsas, and 15.47 mpsas. The beginning of fajr prayer time produced by SQM is after the beginning of fajr prayer time obtained using the Accurate Times concerning the Sun's altitude 18o below the horizon. The difference obtained by SQM directed to the zenith, eastern horizon, and western horizon is 29.5 minutes, 36.7 minutes, and 39.5 minutes. In other words, the beginning of Fajr prayer time used in Indonesia is earlier than it should be.